(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Healthcare sector is shifting focus on improving services by adopting new technological approaches. This enriches the functional characteristics of diagnostic data. With the increase in need of Medical services and lack of availability of the resources, Healthcare Chatbot is an attempt to assist common people with primary health care by reducing the burden on medical frontline workers. The objective of this research work is to design a 24/7 available chatbot that answers common medical queries, predicts diseases based on the symptoms and radiology images provided, aids with medication/ precautionary measures that are to be followed. A chatbot can provide a customized one on one interaction through text or voice interface and gives reply using Artificial Intelligence. It responds differently to messages containing certain keywords and uses Machine Learning to adapt their responses to fit the situation. The healthcare chatbot handles a large number of requested queries at a time making it reliable to use. The chatbot responds to medical queries only to the best of its knowledge database.